Why do we itch?. Issue 12 (28th August 2019) - Lerner, Ethan A.
Abstract: Why do we have the sensation of itch and the associated scratching response? The conventional explanation is that arthropods and other environmental irritants elicit the sensation of itch that then leads to scratching and removal of the stimulus. This explanation is reasonable yet is too limiting for this fascinating sensory phenomenon and the associated somatic (voluntary) response of scratching. We delve into other explanations here. Some of these explanations fit within current areas of basic and clinical knowledge while others are speculative and may help to frame future discussions and study.